The "B" in BPM stands for Business differentiating pure-play BPM from rebranded EAI and workflow technologies. - Treier, Karl
The use of the term BPM (business process management) is becoming increasingly confused as former EAI vendors claim BPM capability and the lines between BPM + SOA and ESB applications are blurred. This article will differentiate what is unique and distinct about BPM compared to other technologies such as EAI (enterprise application integration) and ESB (enterprise service bus) and it will also attempt to characterize what exactly constitutes a Business Process as opposed to an Application Integration, Web Service Orchestration or Data Translation problem. All the while we will be remembering and focusing on the fact that the "B" in BPM stands for Business.